ANALYSIS OF THE EFFECT OF ECONOMIC GROWTH AND HUMAN DEVELOPMENT INDEX ON INCOME INEQUALITY IN THE REGENCIES/CITIES OF SOUTH SULAWESI PROVINCE - M. Adeliani Laksmi Dewi; Surya Dewi Rustariyuni (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Income inequality remains one of the primary challenges in achieving sustainable economic development, particularly in regions endowed with abundant resources but facing uneven income distribution. South Sulawesi Province is recognized as a key economic growth center in Eastern Indonesia; however, it still ranks among the provinces with the highest levels of income inequality nationwide. This study aims to analyze the effect of economic growth and the Human Development Index (HDI) on income inequality across 24 regencies/municipalities in South Sulawesi Province over the period 2014–2023. The analytical method employed is panel data regression using the Fixed Effect Model (FEM) approach. The findings reveal that, simultaneously, both independent variables have a significant effect on income inequality. Partially, HDI has a significant negative effect, while economic growth does not significantly influence income inequality. These results highlight that enhancing human capital and ensuring equitable distribution of development outcomes are key to reducing income inequality at the regional level. The study provides policy implications for local governments to focus more on human resource development and the equalization of development across regions.